Implementation of College Management System - Kumar, A Suraj; Kiran, Y. Naga Surya; Sirisha, P; Srinivas, CH; Begum, Sheik Gousia (International Journal of Computer Sciences and Engineering, 2020)
College Management System is an automated version of student management system. The modules that are managed in this college management system are student personal details, student academic details, student exam result details. These are managed by an administrator. In this college management system the administrator side is designed a web panel with web scraping, where as the student side is designed as Android app. College Management System as categorize into different modules. The following modules are Andhra University Student exam results automation, Certificate Vault designed for both admin and student as web application and Android app, Student complete profile/academic details along with digital study resources.